Nyemendo's Music Composition: Technical and Empirical Verification of the Transformation of the Three Philosophical Values of the Premarital Tradition of the Orang Rimba - Hadaci Sidik; Aluna; Ferry Herdianto; Ahmad Zaidi; Weldi Syaputra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
The premarital tradition of Nyemendo indigenous Orang Rimba in Jambi contains three philosophical values: active patience, practical competence, and communal decisions. These three values have been ethnographically documented by researchers before, but they have never been transformed into musical works and their success has been verified. This article discusses the creation of a three-part musical composition program (exposition, development, recapitulation) with the aim of answering musical questions, namely: what kind of sound represents active patience, what kind of sound represents practical competence, what musical parameters translate active patience into habitus, and what kind of instrumentation represents communal decision. This study uses three theoretical frameworks: Bourdieu's habitus for the social dimension, Tarasti's musical semiotics for the musical sign dimension, and Feld's acoustemology for the dimension of sound as knowledge. Based on this framework, three compositional concepts were formulated: static minimalism for active patience, gestural virtuosity for practical competence, and discontinuous alternation without soloist initiative for communal decisions. The musical material comes from the main notes of the Orang Rimba ritual mantras as well as the sounds of the forest which are treated as materials equivalent to the tone. The results of technical verification through score analysis proved the existence of the three concepts in 139 beats with a duration of 18 minutes. The results of empirical verification through a hearing test with three respondents (composers, art practitioners, and Tumenggung Urip as traditional elders) showed an average score of 4.33 for active patience, 4.67 for practical competence, and 4.33 for communal decisions (scale 1–5). This composition succeeded in filling the research gap by presenting Nyemendo's philosophical values into a verified sound medium.